2006
DOI: 10.1002/ardp.200600077
|View full text |Cite
|
Sign up to set email alerts
|

New Lanthanum (III) Complex – Synthesis, Characterization, and Cytotoxic Activity

Abstract: The complex of lanthanum (III) was synthesized reacting the respective inorganic salt with 5-aminoorotic acid in amounts equal to the metal:ligand molar ratio of 1:3. The complex was prepared by adding an aqueous solution of lanthanum (III) nitrate to an aqueous solution of the ligand, subsequently raising the pH of the mixture gradually to approx. 5.0 through addition of a dilute solution of sodium hydroxide. The structure of the final complex was determined by means of spectral data (IR, Raman,( 1)H-NMR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…After 48 h of 2 mM Eu 3+ addition, the DCM lifetime distribution shifts to 1003–2069 ps with a maximum at ∼1690 ps. This type of inhibition is postulated by the complex formation between Eu 3+ and orotic acid through COO – as reported earlier, and the morphological changes due to lanthanide complex formation also bring new insight into the field of supramolecular chemistry. Again, Banerjee et al have completely blocked the COO – group of orotic acid by esterification, i.e., the synthesis of methyl orotate.…”
Section: Single Nucleobase Self-assemblysupporting
confidence: 59%
“…After 48 h of 2 mM Eu 3+ addition, the DCM lifetime distribution shifts to 1003–2069 ps with a maximum at ∼1690 ps. This type of inhibition is postulated by the complex formation between Eu 3+ and orotic acid through COO – as reported earlier, and the morphological changes due to lanthanide complex formation also bring new insight into the field of supramolecular chemistry. Again, Banerjee et al have completely blocked the COO – group of orotic acid by esterification, i.e., the synthesis of methyl orotate.…”
Section: Single Nucleobase Self-assemblysupporting
confidence: 59%
“…In the last years the potential application of coumarins with metal complexes as cyto-selective therapeutic agents for cancer therapy gained growing interest. Complexes of coumarins with lanthanum(III), zirconium(IV) or cerium(III) represent interesting metalorganic compounds with antitumor activity in different cell lines [19,[87][88][89][90]. The cytotoxicity of the lanthanum complex of bis-coumarins in the chronic myeloid leukemia cell line is partly mediated by the stimulation of programmed cell death whereas the inorganic salt exerts a very weak cytotoxic effect [90].…”
Section: Apoptosis-inducer Agentsmentioning
confidence: 99%
“…Given that the ligands used are well-known biologically active compounds, we compared them with the lanthanide(III) complexes which we have characterized. [22][23][24][25][26]28,29 Detailed analysis of AOA and Ln(III)-AOA systems revealed that the binding mode in the complexes was bidentate through the carboxylic oxygen atoms. It has been suggested that CCA binds to Ln(III) ions through both oxygen atoms of the carboxylic and carbonylic groups.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the lanthanide(III) complexes of AOA and CCA as well as their theoretical, analytical, spectral, and structural characterization have been previously reported by us. [22][23][24][25][26]28,29 Shortly: the compounds used for preparing the solutions were Merck products, p.a. grade:…”
Section: Complexesmentioning
confidence: 99%
See 1 more Smart Citation